Photosynthetic microbial desalination cell (PhMDC) using Chlamydomonas sp. (UKM6) and Scenedesmus sp. (UKM9) as biocatalysts for electricity production and water treatment - Nadzri N.A.A.; Mohd Yasin N.H.; Abu Bakar M.H.; Thanakodi S.; Salehmin M.N.I.; Takriff M.S.; Ni Aznan M.F.; Maeda T. (Elsevier Ltd, 2024)
A current Microbial Desalination Cell (MDC) system often uses chemicals or air cathodes that are toxic and impractical for scalable applications. This work presents the MDC performance that utilized microalgae species Chlamydomonas sp. (UKM6) and Scenedesmus sp. (UKM9). These species supported the role of the terminal electron acceptor in the cathode chamber of photosynthetic MDCs (PhMDC). The results showed that PhMDC-UKM9 and UKM6 produced 1942 mW/m3 and 1714 mW/m3 power densities with 44% and 32% desalination rates, respectively. The desalination of salt concentration (35 g/L) was approaching the practical application of seawater. Both UKM6 and UKM9 achieved chemical oxygen demand (COD) removal in the anode chamber by 49% and 53%, respectively. 16S microbial community analysis in anolyte revealed phylum Firmicutes as the dominion community. This study demonstrated that the local microalgae species integrate power production, wastewater treatment, and water purification through PhMDC operation, comparable with other studies using commercial microalgae. 2023 Hydrogen Energy Publications LLC